Engineered anti-CRISPR proteins for optogenetic control of CRISPR-Cas9 - Bubeck, Felix; Hoffmann, Mareike; Bietz, Andreas; Waldhauer, Max; Börner, Kathleen; Fakhiri, Julia; Schmelas, Carolin; Dietz, Laura; Grimm, Dirk; Eils, Roland; Niopek, Dominik (Nature methods, 2018)
Anti-CRISPR proteins are powerful tools for CRISPR–Cas9 regulation; the ability to precisely modulate their activity could facilitate spatiotemporally confined genome perturbations and uncover fundamental aspects of CRISPR biology. We engineered optogenetic anti-CRISPR variants comprising hybrids of AcrIIA4, a potent Streptococcus pyogenes Cas9 inhibitor, and the LOV2 photosensor from Avena sativa. Coexpression of these proteins with CRISPR–Cas9 effectors enabled light-mediated genome and epigenome editing, and revealed rapid Cas9 genome targeting in human cells.